Campos errantes: práticas investigativas sobre formas de presença - Nogueira, Maria Beatriz Gomes [UNESP] (Universidade Estadual Paulista (Unesp), 2020)
Esta dissertação consiste em um memorial circunstanciado apresentado em duo: texto reflexivo e compilado de imagens. São abordadas conexões entre corpo, materialidades elementares, ação in situ e espaço. Descreve-se e discute-se um conjunto de procedimentos investigativos acerca da instalação campos errantes ancorada por trabalhos anteriores, registros de processo, influências poéticas e conceituais que integram e imprimem sentido à construção da obra. Entrelaçam-se à prática, reflexões em torno de corporeidades, memórias, noções de atenção e experiência, invenção de modos de fazer contextualizados ao ambiente, a caminhadas diárias, a atividade em ateliê e a situações expositivas.

The present dissertation consists of an elaborated memorial displayed in duo: a reflective text and a collection of images. The work approaches connections among body, elementary materiality, in situ action and space. A group of investigative procedures is described and discussed concerning the installation rambling fields which is connected to previous works, process studies, poetic and conceptual influences that complete and give sense to the construction of the artwork. Thoughts about corporealities, memories, notions of attention and experience, practice means invention connected to the environment, daily walks, studio activities and exhibit situations are intertwinded to the practice.
Rambling fields: investigative practices on means of presence
Keywords: Arte contemporânea; Processo de criação; Instalação; Corpo; Espaço; Desenho; Contemporary art; Process of artistic creation; Installation; Body; Space; Drawing